NMR spectroscopic and thermodynamic studies of the etherate and the a, a', and γ phases of AlH3 - Humphries, Terry; Munroe, K.; Dewinter, T.; Jensen, C.; McGrady, G. (2013)
Aluminum hydride (alane; AlH3) has been identified as a leading hydrogen storage material by the US Department of Energy. With a high gravimetric hydrogen capacity of 10.1 wt.%, and a hydrogen density of 1.48 g/cm3, AlH3 decomposes cleanly to its elements above 60 °C with no side reactions. This study explores in detail the thermodynamic and spectroscopic properties of AlH3; in particular the α, α′ and γ polymorphs, of which α′-AlH3 is reported for the first time, free from traces of other polymorphs or side products. Thermal analysis of α-, α′-, and γ-AlH3 has been conducted, using DSC and TGA methods, and the results obtained compared with each other and with literature data. All three polymorphs were investigated by 1H MAS-NMR spectroscopy for the first time, and their 27Al MAS-NMR spectra were also measured and compared with literature values. AlH3·nEt2O has also been studied by 1H and 27Al MAS-NMR spectroscopy and DSC and TGA methods, and an accurate decomposition pathway has been established for this adduct.